Evaluation of Green Productivity Implementation for Measuring Environmental Performance in The Dakron Pillow Production Process at Cv. Jesselyne - Margo Dwi Kusuma Sugiarto; Ardana Putri Farahdiansari; Rio Candra Pratama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to evaluate the application of the Green Productivity concept in the production process of dacron pillows at CV. Jesselyne. Green Productivity is an approach that integrates increased productivity with reduced environmental impacts, in order to achieve industrial sustainability. The methods used include Material Balance analysis to measure the efficiency of raw material utilization and the level of waste generated, as well as the calculation of the Benefit-Cost Ratio (BCR) to assess the economic feasibility of implementing the strategy. The results of the study indicate that the application of Green Productivity is able to increase the efficiency of the production process and reduce waste significantly. The BCR value obtained is 1.52, indicating that each investment made provides economic benefits that exceed its costs, making it feasible to implement. Thus, the application of Green Productivity is proven to be effective as a strategy to improve environmental performance while strengthening the economic aspects of the industrial production process.